Formative student-authored question bank: perceptions, question quality and association with summative performance. Issue 1108 (2nd September 2017) - Walsh, Jason L; Harris, Benjamin H L; Denny, Paul; Smith, Phil
Abstract: Purpose of the study: There are few studies on the value of authoring questions as a study method, the quality of the questions produced by students and student perceptions of student-authored question banks. Here we evaluate PeerWise, a widely used and free online resource that allows students to author, answer and discuss multiple-choice questions. Study design: We introduced two undergraduate medical student cohorts to PeerWise (n=603). We looked at their patterns of PeerWise usage; identified associations between student engagement and summative exam performance; and used focus groups to assess student perceptions of the value of PeerWise for learning. We undertook item analysis to assess question difficulty and quality. Results: Over two academic years, the two cohorts wrote 4671 questions, answered questions 606 658 times and posted 7735 comments. Question writing frequency correlated most strongly with summative performance (Spearman's rank: 0.24, p=<0.001). Student focus groups found that: (1) students valued curriculum specificity; and (2) students were concerned about student-authored question quality. Only two questions of the 300 'most-answered' questions analysed had an unacceptable discriminatory value (point-biserial correlation <0.2). Conclusions: Item analysis suggested acceptable question quality despite student concerns. Quantitative and qualitative methods indicated that PeerWise is a valuable study tool.